Fenomena Safari Maulid Arbain Di Kampung Nimbokrang, Kabupaten Jayapura: Studi Living Quran-Hadis - Agus Rahman Setiawan (POROS ONIM: Jurnal Sosial Keagamaan, 2022)
The commemoration of the Prophet's birthday as a culture has different forms in society. This is influenced by differences in space and culture which then makes a different way someone perceives the text. One form that can be said to be unique is the Maulid Arbain Safari which was held in Nimbokrang Village. Its implementation, which is carried out by moving from one house to another, is one of its unique features. This paper aims to look at the form of implementation, the text, and how this event is interpreted by the actors in it. This study uses the living Quran-Hadith model with qualitative research and analyses with the theory of the sociology of knowledge by Karl Mannheim. The results found from the analysis process show that there are three meanings in this event, namely the objective meaning, which refers to the typical Muslim action of the birth of the Prophet Muhammad, namely to celebrate it with prayer and learn and apply his teachings in a breath. Expressive meaning in which each person is different, for example, is interpreted as a means of increasing knowledge, a means reviving traditions, etc. The meaning of the documentary is that this celebration shows the view of the Islamic world which beliefs in the Prophet Muhammad as a great messenger and the most perfect human being.